2015
DOI: 10.14202/vetworld.2015.1321-1325
|View full text |Cite
|
Sign up to set email alerts
|

Staining of Platyhelminthes by herbal dyes: An eco-friendly technique for the taxonomist

Abstract: Aim:An environment compatible technique to stain Platyhelminthes, Fasciola gigantica, Gastrothylax crumenifer, Taenia solium, and Moniezia expansa using aqueous and alcoholic extract of sugar beet (Beta vulgaris), China rose (Hibiscus rosa-sinensis), and red rose (Rosa hybrida) were described to minimized the deleterious effects of the synthetic dyes.Materials and Methods:Aqueous/ethanolic extracts of roses were extracted from the flowers while red beet was extracted from the roots.Results:Stained helminthes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 7 publications
(8 reference statements)
4
25
0
Order By: Relevance
“…The aqueous and ethanol extracts of beetroot appeared dark red to red in color and maintained staining ability when stored in a refrigerator at 4 ° C. This is similar to other reports [10,13]. Both extracts showed an acidic pH of 5.5 when examined with a pH meter, which is comparable to slightly acidic in [10], pH of 5.2 in [8], and pH 5.4 in [13].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The aqueous and ethanol extracts of beetroot appeared dark red to red in color and maintained staining ability when stored in a refrigerator at 4 ° C. This is similar to other reports [10,13]. Both extracts showed an acidic pH of 5.5 when examined with a pH meter, which is comparable to slightly acidic in [10], pH of 5.2 in [8], and pH 5.4 in [13].…”
Section: Discussionsupporting
confidence: 87%
“…The betalain pigments responsible for this red color have been used in staining of parasites and ova of nematodes [2,3,10]. In this study, the physicochemical and spectrophotometric properties of aqueous and ethanol extracts of red beetroot were determined and adopted in histological staining of various tissues of an albino rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has colourful flowers ranging from white, yellows and reds. Roses are ornamental plants grown for their flowers in the garden throughout the world [33,34].…”
Section: Henna (Lawsonia Inermis)mentioning
confidence: 99%
“…They have concluded that the extract of roses i.e., red rose followed by China rose, followed by red beet possess the ability to replace the conventional stains in the taxonomic study of Platyhelminthes parasites [33]. Chew Weng Cheng et al, did alternative staining using distilled water and ethanol extracts of Diluted honey has to be mixed with anti-fungals.…”
Section: Henna (Lawsonia Inermis)mentioning
confidence: 99%